PRODUCTION OF LIGHTWEIGHT REFRACTORY INSULATION PANELS ON THE BASIS OF PERLITE - A.S.Mohajer, S.Ghanbarnezhad, L.Sharifi, S.H.Mirhosseini,Y.M.Irvani (International Journal of Research Science and Management, 2014)
For saving energy in industrial furnaces, various forms of insulation are used such as bricks, blocks, castable and fibers. Lightweight refractory insulation panels on the basis of Perlite ( 30 wt.%) with chemical bonding (H3PO4) were successfully prepared by Extruding technique after sintering at 900-1100 °C. Properties such as density, sintering shrinkage percent, permanent linear change (PLC) and cold crushing strength are measured. The particle morphology was directly imaged by using scanning electron microscopy (SEM) and mineral phases present in the samples were determined at room temperature by using X-Ray diffraction patterns. According to results, samples with 30 wt.% Perlite with Phosphate bond in the range of 950-1000 °C to have the desired properties such as strength 30-35 Kgf/cm2 , density 0.42-0.45 g/cm3 and application temperature at 1100 °C.